Weld joint fracture behaviour of HSLA steels dissimilar in strength - Rak, Inoslav (Kovine zlitine tehnologije, 1998)
The effect of strength differences (mismatch) between weld metal and two base metals as well as local variations of strength within weld metal/HAZ zones on the toughness properties were discussed. The significance of local fracture toughness measurement technique was also discussed by comparing the CTOD results of delta5 and British Standard deltaBS. Some differences between the two techniqes were discussed in particular for CGHAZ toughness of similar and dissimilar joints.
Keywords: varjenje; zvarni spoji; jeklo; mehanske lastnosti